Cancer-ID: Toward Identification of Cancer by Tumor-Derived Extracellular Vesicles in Blood - Rikkert, L. G.; Beekman, P.; Caro, J.; Coumans, F. A. W.; Enciso-Martinez, A.; Jenster, G.; Le Gac, S.; Lee, W.; van Leeuwen, T. G.; Loozen, G. B.; Nanou, A.; Nieuwland, R.; et al. (Frontiers in Oncology, 2020)
Extracellular Vesicles (EVs) have great potential as biomarkers since their composition and concentration in biofluids are disease state-dependent and their cargo can contain disease related information. Large tumor-derived EVs (tdEVs, > 1 μm) in blood from cancer patients are associated with poor outcome and changes in their number can be used to monitor therapy effectiveness. Whereas small tumor-derived EVs (<1 μm) are likely to outnumber their larger counterparts, thereby offering better statistical significance, identification and quantification of small tdEVs is more challenging. In the blood of cancer patients, a subpopulation of EVs originate from tumor cells, but these EVs are outnumbered by non-EV particles and EVs from other origin. In the Dutch NWO Perspectief Cancer-ID program, we developed and evaluated detection and characterization techniques to distinguish EVs from non-EV particles and other EVs. Despite low signal amplitudes, we identified characteristics of these small tdEVs that may enable the enumeration of small tdEVs and extract relevant information. The insights obtained from Cancer-ID can help to explore the full potential of tdEVs in the clinic.